Exploring the Relationship Between Physical Care (Hair and Nails) and Reading Ability in Elementary School Children - Yuliastuti, Titien; Aryani, Ine Kusuma (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to explore the relationship between reading skills and physical appearance of elementary school students, especially hair and nail conditions. Using a descriptive qualitative approach, this study involved 50 male elementary school students who were selected purposively from various backgrounds. The variables observed included reading skill level (low, medium, high) as well as hair condition (long or short, clean or dirty) and nails (well-groomed or unkempt). The results of the analysis showed a significant correlation between reading skills and students' physical appearance. Children with well-groomed hair and nails tend to have higher reading skills compared to children whose physical hygiene is less considered. This finding underlines the importance of non-academic factors, such as personal hygiene, in supporting students' cognitive development and academic achievement. Therefore, schools and parents are advised to be more active in paying attention to aspects of physical hygiene as an integral part of the strategy to improve the quality of learning, especially in developing reading skills.